Upaya Pembentukan Kepribadian Islami Santri melalui Layanan Bimbingan Kelompok di Pondok Pesantren Roudlatul Qur’an Metro Lampung - Aisyah, Umi; Setiawati, Rini; Rosnawati, Dela (Jurusan Bimbingan dan Konseling Islam, 2019)
Each Santri who enters the boarding school has a different background both from the regional origin, language and economy. So that this difference often creates problems when they have to adjust to the new environment and new people as well. For this reason, the Islamic Boarding School of the Roudlatul Qur'an Metro made efforts to shape the Islamic personality of the santri using group guidance aimed at shaping the Islamic personality of the santri in accordance with Islamic teachings. This research includes field research with a qualitative approach and is descriptive in nature. Data sources in this study were 3 religious teachers and 5 religious students. Data collection methods were carried out using observation, interviews, and documentation methods. The data analysis technique uses interactive data analysis. The results of the research activities group guidance services carried out 3 times a week with the stages of the group namely the stage of formation, the transition phase and the stage of implementation of activities.